Taxonomic classification of butterflies in Lake Imelda, Ormoc, Leyte - Fran, James; Yong, Armelina (James Fran [and] Armelina Yong, 1987)
A Taxonomic Classification of Butterflies was conducted in Lake Imelda, Ormoc, Leyte from November 1986 to February 1987.